2021
DOI: 10.22392/actaquatr.798584
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant Extracts on the Quality of Sous Vide Meagre (Argyrosomus regius) Fillets

Abstract: This study aimed to determine the changes in the quality of sous vide meagre (Argyrosomus regius) fillets that have been treated with oregano and rosemary extracts during the cold storage (4±1 °C). Saturated fatty acids, monounsaturated fatty acids, and polyunsaturated fatty acids dominant in meagre fish were found to be palmitic acid, oleic acid, and linoleic acid, respectively. pH values fluctuated during storage in sous vide samples. It was determined that total volatile basic nitrogen (TVB-N), thiobarbitur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…It is thought that this situation is caused by both heat treatment and vacuum packaging. Bozova and İzci (2021), no yeast or mold was detected in meagre fillets applied sous vide during the 42-day storage period. Russo et al (2023) noted that mussel samples cooked sous vide at temperatures higher than 80ºC inhibited the growth of yeast and mold.…”
Section: Microbiological Analysismentioning
confidence: 86%
See 1 more Smart Citation
“…It is thought that this situation is caused by both heat treatment and vacuum packaging. Bozova and İzci (2021), no yeast or mold was detected in meagre fillets applied sous vide during the 42-day storage period. Russo et al (2023) noted that mussel samples cooked sous vide at temperatures higher than 80ºC inhibited the growth of yeast and mold.…”
Section: Microbiological Analysismentioning
confidence: 86%
“…In French, sous vide means "under vacuum". The cooking process is generally carried out at low temperatures below 100°C and requires longer cooking time than traditional cooking methods (Bozova, 2020;Yıldız & Yılmaz, 2020;Ceylan, 2021;Öztürk et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, several studies have reported that as heating treatment intensifies (higher temperatures and/or prolonged cooking time), volatiles derived from lipid oxidation decrease, and the content of volatile compounds derived from the degradation of amino acids and/or thiamine increases (del Pulgar et al, 2013;Roldan et al, 2015). Bozova & İzci (2021) found that the addition of rosemary and oregano extracts to SV-cooked meagre (Argyrosomus regius) fillets during refrigeration improved flavor (taste and smell) of fish and had a good antibacterial effect which contributed to control the total number of mesophilic and psychrophilic aerobic bacteria on day 42 of storage (4 ± 1 °C); moreover, contents of total volatile basic nitrogen, thiobarbituric acid, and trimethylamine-nitrogen did not exceed the recommended limits throughout the storage period.…”
Section: Impact On Flavor Of Aquatic Food Productsmentioning
confidence: 97%
“…Minimal temperature treatment employment is the major advantage of SV over other cooking methods. However, some studies report that this low-temperature treatment might not cause complete microbial destruction causing the threat of food-borne diseases (FBD), which can lead to chances of microbiological deterioration, making the process a point of debate for HACCP interpretation. , Therefore, a thorough analysis of the available literature on the same area has been discussed in this article that will be facilitating further research in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, SV along with other hurdles, including freezing, makes it a part of hurdle technology. According to Bozova and Levent, 2 frozen foods subjected to SV have a shelf life of 6−42 days, pursuant to processing time and temperature combination. Minimal temperature treatment employment is the major advantage of SV over other cooking methods.…”
Section: Introductionmentioning
confidence: 99%